REBRANDING STRATEGY FOR COFFEE SMES: NAVIGATING BRAND IDENTITY TRANSFORMATION IN A COMPETITIVE LANDSCAPE - Destriani, Elsa; Yanuar Rahman (Telkom University, 2026)
While the coffee industry in Bandung experiences rapid saturation, many local businesses struggle with brand stagnation and loss of consumer relevance. This study investigates the rebranding strategy of Tovi Kohi, a cafe in East Bandung, focusing on the strategic reconfiguration of brand image to maintain competitive advantage. The research fills a gap in localized rebranding studies within the coffee sector, specifically exploring how visual identity and packaging transformation can recalibrate consumer perception in a niche geographic market. Utilizing a qualitative approach, data were collected through purposive semi-structured interviews with owners and customers, field observations, and document analysis, which were then processed using thematic analysis techniques. Results demonstrate that rebranding success hinges on four critical dimensions: consistent visual identity development, mnemonic brand naming, community-centric marketing, and the implementation of fresh, energetic packaging design—specifically utilizing color psychology (pink/yellow) to attract Gen Z and female demographics. This research contributes to the discourse on brand management by providing a framework for small-scale F&B enterprises to achieve strategic alignment with shifting market preferences.